DIFFERENCE IN THE EFFECT OF TABATA STYLE HIGH INTENSITY INTERVAL TRAINING AND ISOMETRIC EXERCISE ON BLOOD PRESSURE IN OVERWEIGHT-OBESE FEMALE STUDENTS\ (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2025)
Abstract_______________________________________________________ Overweight and obesity are one of the health challenges of Indonesian society. One effective way to prevent and manage the health impact of overweight-obesity through physical exercise is Tabata Style High Intensity Interval Training (HIIT) and Isometric exercise. To determine the effect of Tabata Style HIIT and Isometric exercise on blood pressure in overweight-obese female students at the Faculty of Medicine, University of Palangka Raya. This study used a quassy-experimental quantitative method  with  a two-group pre-post design approach  where the research was divided into two treatment groups, namely the Tabata Style HIIT group and the Isometric exercise group. Based on the results of the Wilcoxon  Tabata Style HIIT TDs,  Isometric TDs, and Isometric TDd  tests of 0.023, 0.008, and 0.031 (p 0.05). The results  of the Paired T-test TDd Tabata Style HIIT were 0.004 (p 0.05). The results of the Mann-Whitney U Test test at the difference between the two exercises showed a  systolic blood pressure P value of 0.698 (p 0.05) and a diastolic blood pressure P value of 0.501 (p 0.05). There was an effect of Tabata Style HIIT and Isometric exercise on blood pressure but there was no difference in the effect  of Tabata Style HIIT and Isometric exercise on blood pressure in overweight-obese female students at the Faculty of Medicine, University of Palangka Raya.